Mapping and direct valuation: do they give equivalent EQ-5D-5L index scores?. Issue 1 (December 2015) - Luo, Nan; Cheung, Yin; Ng, Raymond; Lee, Chun
Abstract Objective Utility values of health states defined by health-related quality of life instruments can be derived from either direct valuation ('valuation-derived') or mapping ('mapping-derived'). This study aimed to compare the utility-based EQ-5D-5L index scores derived from the two approaches as a means to validating the mapping function developed by van Hout et al for the EQ-5D-5L instrument. Methods This was an observational study of 269 breast cancer patients whose EQ-5D-5L index scores were derived from both methods. For comparing discriminatory ability and responsiveness to change, multivariable regression models were used to estimate the effect sizes of various health indicators on the index scores. Agreement and test-retest reliability were examined using intraclass correlation coefficient (ICC). Whenever appropriate, the 90 % confidence intervals (90 % CI) were compared to predefined equivalence margins. Results The mean difference in and ICC between the valuation- and mapping-derived EQ-5D-5L index scores were 0.015 (90 % CI = 0.006 to 0.024) and 0.915, respectively. Discriminatory ability and responsiveness of the two indices were equivalent in 13 of 15 regression analyses. However, the mapping-derived index score was lower than the valuation-derived index score in patients experiencing extreme health problems, and the test-retest reliability of the former was lower than the latter, for example, their ICCs differed by 0.121 (90 % CI = 0.051 to 0.198) in patients who reported no change in performance status in the follow-up survey. Conclusion This study provided the first evidence supporting the validity of the mapping function for converting EQ-5D-5L profile data into a utility-based index score.